Biopiracy versus One-World Medicine-From colonial relicts to global collaborative concepts - Efferth, Thomas; Banerjee, Mita; Abu-Darwish, Mohammad Sanad; Abdelfatah, Sara; Boeckers, Madeleine; Bhakta-Guha, Dipita; Bolzani, Vanderlan [UNESP]; Daak, Salah; Demirezer, Omur Lutfiye; Dawood, Mona; Efferth, Monika; El-Seedi, Hesham R.; et al. (Elsevier B.V., 2019)
Background: Practices of biopiracy to use genetic resources and indigenous knowledge by Western companies without benefit-sharing of those, who generated the traditional knowledge, can be understood as form of neo-colonialism. Hypothesis: The One-World Medicine concept attempts to merge the best of traditional medicine from developing countries and conventional Western medicine for the sake of patients around the globe. Study design: Based on literature searches in several databases, a concept paper has been written. Legislative initiatives of the United Nations culminated in the Nagoya protocol aim to protect traditional knowledge and regulate benefit-sharing with indigenous communities. The European community adopted the Nagoya protocol, and the corresponding regulations will be implemented into national legislation among the member states. Despite pleasing progress, infrastructural problems of the health care systems in developing countries still remain. Current approaches to secure primary health care offer only fragmentary solutions at best. Conventional medicine from industrialized countries cannot be afforded by the impoverished population in the Third World. Confronted with exploding costs, even health systems in Western countries are endangered to burst. Complementary and alternative medicine (CAM) is popular among the general public in industrialized countries, although the efficacy is not sufficiently proven according to the standards of evidence-based medicine. CAM is often available without prescription as over-the-counter products with non-calculated risks concerning erroneous self-medication and safety/toxicity issues. The concept of integrative medicine attempts to combine holistic CAM approaches with evidence-based principles of conventional medicine. Conclusion: To realize the concept of One-World Medicine, a number of standards have to be set to assure safety, efficacy and applicability of traditional medicine, e.g. sustainable production and quality control of herbal products, performance of placebo-controlled, double-blind, randomized clinical trials, phytovigilance, as well as education of health professionals and patients.
Keywords: Complementary and alternative medicine; Evidence-based medicine; Integrative medicine; Nagoya protocol; Quality control; Traditional medicine